2002
DOI: 10.1002/asi.10164
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for a project examining cognitive categories for library information in young children

Abstract: This article presents an overview of some of the methodology used in a project that examined children's understanding of library information and how those perspectives change in the first 5 years of formal schooling. Because our understanding of information is reflected in the manner in which we classify, or typify, that information in order to view the library collection from a child's perspective children were invited to shelve (i.e., classify) terms representative of library books and then to label those ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
1
33
0
5
Order By: Relevance
“…Other research [2] investigated creating a library from a child"s perspective, in which children categorized terms that represented library books and labeled the resulting categories. This previous research supports this approach as it indicates that children are able to group, categorize and name the resulting group based on their own perceptions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research [2] investigated creating a library from a child"s perspective, in which children categorized terms that represented library books and labeled the resulting categories. This previous research supports this approach as it indicates that children are able to group, categorize and name the resulting group based on their own perceptions.…”
Section: Methodsmentioning
confidence: 99%
“…It is known children categrorize things differently to adults [2]. Studies examining how children categorize books for use in a digital library have shown that children categorize this kind of information in a way that makes sense to them, rather than in line with existing categories [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…After the advent of the web, the use of cognitive models looked quite similar in nature. One study examined how children classify information in order to determine how information should be organized in a children's library, while another study looked at how belief changes may influence how people cognitively organize information [107,108]. Despite the continuing use of cognitive models, there has been some critique that these cognitive models do not account for the sociocultural differences which may influence the words people use to retrieve information [109].…”
Section: Cognitionmentioning
confidence: 99%
“…For example, unlike adults, young children (aged 6-7) often are unable to make a clear distinction between fiction and non-fiction (Cooper 2002(Cooper , 1229 and many children (aged 4-7) primarily choose books based on the book's colour or shape rather than the book's contents (Druin 2005, 30). Traditionally, because children are different, separate spaces are created for them in physical libraries.…”
Section: Figure 1 the Topeka And Shawnee County Public Library Websitementioning
confidence: 99%